Do Competitive Examinations Promote Diversity in Civil Service?. (29th April 2019) - Greenan, Nathalie; Lanfranchi, Joseph; L'Horty, Yannick; Narcy, Mathieu; Pierné, Guillaume
Abstract: The representative bureaucracy literature provides a growing body of empirical evidence that a representative public workforce enhances the efficacy and legitimacy of public services. However, little attention has been paid to the capacity of civil service competitive examinations to give equal opportunity of access to public jobs to equally competent citizens. To fill this gap, the authors use French databases to analyze whether competitive examinations comprising both written and oral tests ensure equality of treatment for all candidates regardless of gender, place of residence, or place of birth. The results challenge the capacity of these examinations to treat candidates equally, identifying inequalities in the written tests as well as evaluation biases in the oral tests. However, oral evaluation biases tend to offset inequalities in the written tests. Therefore, selection boards take a sort of affirmative action toward the sole successful members of groups suffering such inequalities .